Museum Technology and Architecture - Rangel, Bárbara; Amorim Faria, José Manuel; Abrantes, Vitor (Building Research: Design, Construction and Technologies, 2019)
This book describes two different museums using construction technology as the common language that brings architecture and engineering together. The first is the Museum of the Ibere Camargo Foundation at Porto Alegre, Rio Grande do Sul, Brazil, by Álvaro Siza and GOP, and the second is the Coach Museum at Lisbon in Portugal, by Paulo Mendes da Rocha and AFAconsult. Both projects put special emphasis on the design process as a construction language, achieved by a close collaboration promoted by the integrated design methodology that both teams follow. Besides its importance from an architectural and urban point of view, these two buildings suggest interesting topics that are present in current building research such as sustainability, the construction of façades with a heavy use of unrendered white concrete and the integration of all the technical infrastructure needed to build a successful high-tech museum. .